Peningkatan Ketrampilan Kader Posyandu Dalam Konseling Laktasi Sebagai Upaya Menggalakkan ASI Eksklusif - Gita Sekar Prihanti; Muhammad Yasirto Fujaya; Thontowi Djauhari; Diah Hermayanti (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2015)
Improving the Skills of Posyandu Cadres in Lactation Counseling as an Effort to Promote Exclusive Breastfeeding Background: During the 3 years of the achievement of exclusive breastfeeding in Puskesmas Kendal Kerep Malang has fluctuated, and only 1 out of 17 people related to the counseling of the breastfeeding who has been trained in breastfeeding counseling. Objective: To determine the effect of breastfeeding counseling training to support health workers in breastfeeding in Puskesmas Kendal Kerep Malang Methods: The study was quasi-experimental design with non-equivalent control group Results: There were differences in the support of health workers (pre-test and post-test) in the control and treatment groups (Wilcoxon test = 0.000 < á 0.05. There were differences in the support of health workers in breastfeeding (pre-test and post-test) in the control and treatment groups (Mann-Whitney = 0.000 < á 0.05). average ratings pre-test and post test both the control group and the treatment of the support of health workers had increased quite dramatically (9.167). Conclusions: There was a positive difference to the health workers support mothers in breastfeeding before and after breastfeeding counseling training. Breastfeeding counseling training was very effective to change the treatment of health workers in support of breastfeeding.